Isolasi Dan Identifikasi Bakteri Asam Laktat Pada Susu Kuda Sumbawa - Nadia Iga Astari, - (2020)
Sumbawa Horse’s milk is the type of dairy horse which has value nutrition similar to cow milk, but it was believed that horse milk more valueable than cow milk.Horses milk has been famous in the past because their nutrition and medical values. The purpose of this research is to knowing description of lactic acid bacteria (LAB) from Sumbawa Horse’s Milk. A study on isolation and identification of lactic acid bacteria from Sumbawa Horse’s Milk, this study aims to isolate lactic acid bacteria and to determine what types of lactic acid bacteria contained in Sumbawa Horse’s Milk. The process of this research began from dilution medium MRSB (De Man Rogosa and Sharpe Broth) up to 10-5 then grown on MRSA (De Man Rogosa and Sharpe Agar) medium and incubated in temperature 37°C for 48 hours using pour plate metode. Lactic acid bacterial colonies were purified by quadran streak method on MRSA medium and incubated in temperature 37°C degree for 48 hours. The next phase morphology observed, macroscopically by looking at the medium form colonies, whereas Gram Microscopic done. Then a biochemical activity test was carried out which included a test of confectionery. The results of the isolation of Lactic Acid Bacteria on MRSA media obtained positive Gram bacterial isolates in the form of bacillus,It is suspected that the isolate was Lactic Acid Bacteria Isolate.